Two rare cases of oral metastasis arising from lung adenocarcinoma and esophageal carcinoma - Rocha, Breno-Amaral (J Clin Exp Dent, 2020)
Metastasis to the oral cavity are rare, representing only 1% of all oral malignancies, and originate from various sites such as the breast, prostate, lung and kidney. Clinically, they can simulate reactive and inflammatory lesions common in the oral cavity, and the clinical and microscopic diagnosis of these metastasis is a challenge. In this article, we report two new cases of esophageal and lung metastasis to oral tissues, highlighting their clinical characteristics and the process of diagnostic elucidation. We emphasize the importance for clinicians to consider the possibility of metastatic lesions in the oral cavity in patients previously diagnosed with malignant lesions in distant tissues and organs. Key words:Diagnosis, esophageal squamous cell carcinoma, adenocarcinoma of lung, oral cavity, metastasis.